Three level T-type inverter with ability fault-tolerant - Le, Hoàng Linh; Ho , Anh Khoa; Quach , Thanh Hải; Tran, Vĩnh Thanh; Do , Đức Trí (Journal of Technical Education Science, 2019)
This paper presents the operation of three-level quasi Z source T-Type in normal and open-circuit switch failure mode (3L qZST2I-UFM). This topology has combined with two main components as quasi Z source (qZS) and three-level T-Type inverter. Besides the advantages of voltage source multilevel inverter, this topology is also capable of overcoming the shoot-through in the traditional multilevel inverter. Furthermore, this topology ensures the stability of the system when any switches of T-type is opened circuit failure. In open-switch circuit fault-tolerant methods of the traditional inverter, the output power will be reduced. However, this disadvantage will be overcome by the characteristic boost of the qZS network. Simulation and Experimental results have presented to verify the control algorithm.